Forest tent caterpillar, Malacosoma disstria (Lepidoptera: Lasiocampidae), mate-finding behavior is greatest at intermediate population densities: implications for interpretation of moth capture in pheromone-baited traps - Evenden, Maya L.; Mori, Boyd A.; Sjostrom, Dana; Roland, Jens (Frontiers in Ecology and Evolution, 2015)
The forest tent caterpillar, Malacosoma disstria Hübner (Lepidoptera: Lasiocampidae) is a native forest defoliator with a broad geographic range in North America. Forest tent caterpillars experience cyclical population changes and at high densities, repeated defoliation can cause reduced tree growth and tree mortality. Pheromone-based monitoring of forest tent caterpillar moths can provide information on spatial and temporal patterns of incipient outbreaks. Pheromone-baited trap capture of male moths correlates to the number of eggs and pupae in a population but this relationship breaks down at high population densities, when moth trap capture declines. The objective of the current study is to understand the mechanisms that reduce trap capture at high population densities. We tested two different hypotheses: 1) at high population densities, male moth orientation to pheromone sources is reduced due to competition for pheromone plumes; and 2) moths from high density populations will be in poor condition and less likely to conduct mate-finding behaviors than moths from low density populations. A field study showed non-linear effects of density on male moth capture in female-baited traps. The number of males captured increased up to an intermediate density level and declined at the highest densities. Field cage studies showed that female moth density affected male moth orientation to female-baited traps, as more males were recaptured at low than high female densities. There was no effect of male density on the proportion of males that oriented to female-baited traps. Moth condition was manipulated by varying larval food quantity. Although feeding regimes affected the moth condition (size), there was no evidence of an effect of condition on mate finding or close range mating behavior. In the field, it is likely that competition for pheromone plumes at high female densities during population outbreaks reduces the efficacy of pheromone-baited monitoring traps.